A brain for all seasons: An in vivo MRI perspective on songbirds. Issue 9 (21st August 2022) - Orije, Jasmien Ellen Maria Jozef; Van der Linden, Annemie
Abstract: Seasonality in songbirds includes not only reproduction but also seasonal changes in singing behavior and its neural substrate, the song control system (SCS). Prior research mainly focused on the role of sex steroids on this seasonal SCS neuroplasticity in males. In this review, we summarize the advances made in the field of seasonal neuroplasticity by applying in vivo magnetic resonance imaging (MRI) in male and female starlings, analyzing the entire brain, monitoring birds longitudinally and determining the neuronal correlates of seasonal variations in plasma hormone levels and song behavior. The first MRI studies in songbirds used manganese enhanced MRI to visualize the SCS in a living bird and validated previously described brain volume changes related to different seasons and testosterone. MRI studies with testosterone implantation established how the consequential boost in singing was correlated to structural changes in the SCS, indicating activity‐induced neuroplasticity as song proficiency increased. Next, diffusion tensor MRI explored seasonal neuroplasticity in the entire brain, focusing on networks beyond the SCS, revealing that other sensory systems and even the cerebellum, which is important for the integration of sensory perception and song behavior, experience neuroplasticity starting in the photosensitive period. Functional MRI showed that olfactory, and auditory processing was modulated by the seasons. The convergence of seasonal variations in so many sensory and sensorimotor systems resembles multisensory neuroplasticity during the critical period early in life. This sheds new light on seasonal songbirds as a model for unlocking the brain by recreating seasonally the permissive circumstances for heightened neuroplasticity. Abstract : Longitudinal magnetic resonance imaging studies unravelled photoperiod, singing‐activity induced and hormonally modulated neuroplasticity in a seasonal songbird (European starling). This neuroplasticity extended beyond the song control system (SCS) in multiple sensory systems (including the auditory, visual and olfactory system) and the cerebellum. RESEARCH HIGHLIGHTS: Longitudinal MRI studies unraveled photoperiod, singing‐activity induced and hormonally modulated neuroplasticity in a seasonal songbird (European starling). This neuroplasticity extended beyond the song control system including multiple sensory systems and the cerebellum.